2018
DOI: 10.3390/ijerph15122903
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Happiness and Cohesion in the Relationship between Employee Volunteerism and Job Performance

Abstract: This study investigated the mediating effects of happiness and cohesion in the relationship between employee volunteerism, in-role behavior, and helping behavior. The study surveyed 312 full-time employees in South Korea, and regression analyses and the bootstrapping method were used to test the hypotheses. The study found happiness and cohesion to mediate the relationships between employee volunteerism and in-role and helping behavior. The findings suggest that employee volunteerism can promote a healthy work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…The most unanticipated finding in the current study was the mediating effect of job satisfaction on the association between group cohesion and quality of nursing handovers among psychiatric nurses, which suggests that group cohesion not only directly influences the quality of nursing handovers but also indirectly the quality of nursing handovers via job satisfaction. Prior surveys have revealed an association between group cohesion and job satisfaction; in particular, group cohesion is beneficial to nurses, both in terms of job satisfaction [ 42 ]. Other studies have shown that nurses participate in power-sharing activities, foster a collaborative work environment, and demonstrate greater job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The most unanticipated finding in the current study was the mediating effect of job satisfaction on the association between group cohesion and quality of nursing handovers among psychiatric nurses, which suggests that group cohesion not only directly influences the quality of nursing handovers but also indirectly the quality of nursing handovers via job satisfaction. Prior surveys have revealed an association between group cohesion and job satisfaction; in particular, group cohesion is beneficial to nurses, both in terms of job satisfaction [ 42 ]. Other studies have shown that nurses participate in power-sharing activities, foster a collaborative work environment, and demonstrate greater job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that positive emotions make employees stay optimistic and enthusiastic, energetic and confident in their work, active in accomplishing goals and tasks, and improve job performance (Ouweneel et al, 2012). Therefore, positive emotions have a significant positive effect on job performance (Yavas et al, 2013;Im et al, 2018;Reizer et al, 2019).…”
Section: The Mediating Role Of Subordinates' Positive Emotionsmentioning
confidence: 99%
“…Job performance refers to behaviors and results that employees show in their work and are closely related to their goals (Rich et al, 2010). Employees' emotions have a significant impact on their job performance (Grobelna, 2019;Moin et al, 2020), such as negative emotions like anger and sadness, can reduce employees' job performance (Rispens and Demerouti, 2016;Saulnier et al, 2020), and positive emotions, such as happiness and hope, can increase performance (Yavas et al, 2013;Im et al, 2018). However, with the acceleration of competition, excessive mental stress and emotional exhaustion have seriously affected employees' performance (Janssen et al, 2020;Tome and van der Vaart, 2020), and it is more prominent for employees in rapidly developing Chinese organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of employee volunteerism creates self-internationalisation of a volunteer identity, which increases the firm’s quality of programmes and projects (van Schie et al, 2019 ). The internationalisation breeds benefits, including the improvement of pride and trust (Im & Chung, 2018 ) and happiness and cohesion (Im et al, 2018 ). It is argued that CSR and employee volunteering affect consumers’ behaviour towards product consumption (Jin et al, 2017 ).…”
Section: Theory Literature Review and Hypotheses Developmentmentioning
confidence: 99%